DDRE-14. OPTIMIZING MDM2 INHIBITION FOR THE TREATMENT OF HIGH-GRADE GLIOMA. (12th November 2021) - Rendo, Veronica; Lupien, Leslie; Khuu, Nicholas; Pelton, Kristine; Elcavage, Lara; Lu, Sophie; Khadka, Prasidda; Langhnoja, Jaldeep; Phoenix, Tim; Ligon, Keith; Bandopadhayay, Pratiti; Beroukhim, Rameen
Abstract: A majority of high grade gliomas retain a wild-type TP53 gene and are amenable to strategies for activation of the pathway to inhibit tumor growth. The interaction between p53 and MDM2 has served as target for such strategies currently in clinical trials for glioblastoma. As the effects and resistance mechanisms of MDM2 inhibition (MDM2i) remain poorly understood in glioma, we performed genomic and transcriptomic analyses in patient-derived models to better characterize sensitive tumors and identify putative biomarkers of drug response. Treatment with an MDM2 inhibitor (KRT232/AMG232) impaired the growth of cell lines with wild-type TP53 status, particularly in tumors with amplification of MDM2/4 or PPM1D activating mutations. Treatment with KRT232 upregulated both cell cycle arrest and apoptotic cellular responses, with unique temporal and transcriptional differences correlated with MDM2/4 or PPM1D status. In other tumors resistance to MDM2i is mainly mediated by TP53 mutations, but in a subset of chronic KRT232-treated glioma models we noted lack of TP53 mutations and identified cell state and transcriptional changes as potentially more treatable mediators of resistance.